Alveolar macrophage phagocytic activity is enhanced with LPS priming, and combined stimulation of LPS and lipoteichoic acid synergistically induce pro-inflammatory cytokines in pigs. Issue 6 (December 2013) - Islam, Mohammad Ariful; Pröll, Maren; Hölker, Michael; Tholen, Ernst; Tesfaye, Dawit; Looft, Christian; Schellander, Karl; Cinar, Mehmet Ulas
The objective of the present study was to investigate LPS and lipoteichoic acid (LTA)-induced TLRs, associated signaling molecules and inflammatory mediators, as well as to compare their combined effect in porcine alveolar macrophages. Macrophages were incubated for 24 h with various concentrations of LPS, LTA, LPS + LTA or control. Multiple concentrations of LPS elicited marked up-regulation in mRNA for TLR2 and TLR4, CD14, MD2, MyD88, IRAK-4 and TRAF6 compared with the control. LTA had no effect on TLR4 and MD2; only higher doses up-regulated TLR2, CD14, MyD88, IRAK-4 and TRAF6 mRNA. LPS-activated cells released IL1-β, IL12-β, TNF-α, IL-6, IL-8, IFN-γ and IL-10 in a dose-dependent manner, while LTA had no effect on IL-1β, IL-6 and IFN-γ. Higher doses of LTA induced IL-12β, TNF-α, IL-8 and IL-10. Combined stimulation augmented TLR2, CD14 and MyD88 mRNA, and subsequently produced elevated levels of IL-6, TNF-α and IL-8 when compared with LPS and LTA alone. Additionally, phagocytosis of macrophages was significantly increased following low concentration of LPS treatment. Only low levels of NO (nitric oxide) were detected in the LPS group. Overall, compared with LPS, LTA was a relatively weak inducer, and co-stimulation accelerated gene and cytokine production associated with pulmonary innate immune function.